Pengembangan Prototipe Robot Pengaduk Menggunakan Sensor Suhu dan Kelembaban untuk Memantau Tingkat Kekeringan Gabah Berbasis Internet of Things - Anjas Saswito; Musfirayanti Musfirayanti; Remigius Tandioga; Imran Habriansyah (Politeknik Negeri Ujung Pandang, 2022)
Drying grain requires a large area with heavy work because farmers have to turn the grain that lies on the field every hour and requires a lot of energy because it is done under the hot sun. Drying of grain by farmers involves still checking the level of dryness manually using only the human senses as a measuring tool. One of the drawbacks is that manual checking process is not accurate enough and will affect rice production. So we need an innovation in existing technology to measure the level of drought.This robot is designed in the form of a prototype where the grain mixer system is in the middle. The movement of the robot is only forward and backward which will be controlled using a smartphone by the operator and the width of the grain area to be stirred is 50 cm or along the stirrer. Temperature and humidity sensors will be installed at the bottom which will make it easier to measure the temperature and humidity of the stirred grain making it easier for farmers to monitor the level of grain dryness.